2005
DOI: 10.1177/1043986205282018
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Thoughtlessness in Prisons and Its Impacts on the Day-to-Day Prison Lives of Elderly Men

Abstract: The number of elderly men in the prisons of England and Wales has grown significantly during the past decade and continues to rise. Based on intensive fieldwork in four English prisons, this article explores the prison experiences of menaged 65+ years. Some of these menhave grownold in prison, some have served previous prison sentences, and others (the majority) have been sentenced to a term of imprisonment in later life. The latter had no prior experience of imprisonment. This article is concerned primarily w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
100
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 6 publications
6
100
0
1
Order By: Relevance
“…Previous research has shown that, if health needs are not picked up at reception or very quickly afterwards, they tend to remain unaddressed throughout someone's whole sentence. 61 Our study showed that the OHSCAP was often delayed and thus decisions around a person's care and safety (including appropriate location, access to prison facilities, suitable work/vocational activities and care needs around assistance needed for dressing, washing or mobilisation) could be being taken without the comprehensive information required to inform such decision-making, leaving the person potentially at risk or unable to maintain their care needs. We would argue that this is fundamental to the decency agenda and that an overall review of the processes and systems that operate during an early custody induction period needs to ensure that the most important processes are implemented early and inform the remaining processes.…”
Section: Implications Of the Findingsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research has shown that, if health needs are not picked up at reception or very quickly afterwards, they tend to remain unaddressed throughout someone's whole sentence. 61 Our study showed that the OHSCAP was often delayed and thus decisions around a person's care and safety (including appropriate location, access to prison facilities, suitable work/vocational activities and care needs around assistance needed for dressing, washing or mobilisation) could be being taken without the comprehensive information required to inform such decision-making, leaving the person potentially at risk or unable to maintain their care needs. We would argue that this is fundamental to the decency agenda and that an overall review of the processes and systems that operate during an early custody induction period needs to ensure that the most important processes are implemented early and inform the remaining processes.…”
Section: Implications Of the Findingsmentioning
confidence: 99%
“…Participants reported that prison officers often lacked insight into older prisoner issues. This has previously been described as 'institutionalised thoughtlessness' by Crawley, 61 and defined as 'the ways in which prison regimes (routines, rules, time-tables, etcetera) simply roll on with little reference to the needs and sensibilities of the old'. The findings from this research suggest that such thoughtlessness is still apparent in prisons in England and Wales.…”
Section: Implications Of the Findingsmentioning
confidence: 99%
See 3 more Smart Citations